Editorial: targeting aberrant hepatic inflammation for treatment of non‐alcoholic steatohepatitis—authors' reply. Issue 4 (28th January 2022) - Safadi, Rifaat; Braun, Marius; Francis, Adi; Milgrom, Yael; Massarwa, Muhammad; Hakimian, David; Hazou, Wadi; Issachar, Assaf; Harpaz, Zivit; Farbstein, Motti; Itzhak, Inbal; Lev‐Cohain, Naama; et al.
LINKED CONTENT: This article is linked to Safadi et al papers. To view these articles, visit https://doi.org/10.1111/apt.16664 and https://doi.org/10.1111/apt.16748